In vitro Membrane Stabilizing and In vivo Analgesic Activities of Boehmeria glomerulifera Miq. in Swiss-Albino Mice Model (Bangladesh Pharmaceutical Journal, 2016)
Boehmeria glomerulifera Miq. is an indigenous plant of Bangladesh. Traditional healers use this plant to treat various diseases. The crude methanol extract of whole plant of B. glomerulifera and its Kupchan fractions were screened for in vitro membrane stabilizing and only the crude extract at doses of 200- and 400- mg/kg body weight were screened for analgesic activity in mice model in order to establish the medicinal values of this plant. The membrane stabilizing activity of the extractives was evaluated by the ability of test materials to inhibit hypotonic solution- and heat-induced haemolysis of human erythrocytes. Moreover, the analgesic activity of methanol extract was evaluated by acetic acid induced writhing method and tail immersion method in mice. In hypotonic solution- and heat-induced conditions, the crude methanol extract showed inhibition of haemolysis by 64.80±0.34% and 21.63±0.76%, respectively as compared to 77.74±0.67% and 40.41±0.69% demonstrated by the standard, acetyl salicylic acid. On the other hand, the analgesic activity was determined for its peripheral and central pharmacological responses using acetic acid-induced writhing test and tail immersion method at doses of 200- and 400- mg/kg body weight. The extract reduced the acetic acid-induced writhings significantly (p < 0.05) in a dose dependent manner with the highest activity observed at 400 mg/kg (46.0%) body weight when compared to that of Diclofenac sodium (64.0%), as the standard drug. A significant increase (p < 0.01) of latency period was also found in tail immersion method. Therefore, the present study established that the methanol extract of B. glomerulifera possesses moderate membrane stabilizing and significant analgesic activities.Bangladesh Pharmaceutical Journal 19(2): 185-189, 2016